Use of Phytase to Enhance Nutritional Value of Broiler Breeder Diets - Nusairat, B.; Qudsieh, R.; Brake , J. (International Journal of Poultry Science, 2018)
Objective: This study was designed to determine the effects of dietary phytase on broiler breeder grower and layer diets. Materials and Methods: Chicks received a common starter diet up to 42 days of age. Treatments were 0 (control), 300, 600 and 1200 FTU kg–1 phytase feed applied from 43 days to 4 replicate pens per treatment. Dietary calcium (Ca) was 0.7 and 2.7% while available phosphorus (AvP) was 0.35 and 0.12%, in the control grower and layer diets, respectively. Egg production, hatchability, fertility, egg quality, bone breaking strength, body weight (BW) and mortality to 64 weeks of age were measured. Data were analyzed using one-way ANOVA in 10 weeks quartile periods from 25-64 weeks of age as well as on an overall basis. Results: During the first quartile, phytase increased (p<0.05) egg production with 300 FTU when compared to the control with the 600 and 1200 FTU diets intermediate. All phytase treatments increased (p<0.05) egg production compared to the control on overall basis and during the final quartile (56-64 weeks), hatchability of fertile eggs was increased (p<0.05) by 600 and 1200 FTU phytase relative to the control with 300 FTU intermediate during the fourth quartile. Fertility, egg weight, shell thickness and bone breaking strength were not affected. Conclusion: As evidenced by increased egg production without effect on fertility, egg shell quality or bone strength, it was concluded that 300 FTU of phytase was sufficient to liberate adequate Ca and AvP as well as additional metabolizable energy (ME) but not crude protein (CP) in broiler breeder grower and layer diets.